The Performance qualification of automatic volumetric pipettes used in university hospitals in the DRC: Case of Kinshasa, Bukavu, and Kisangani - Joenna Bapite Musongiela; Jocelyn Mankulu Kakumba; Emile Tweni Baruti; Timothé Mavanga Mabaya; Jacquie Bolavie Bolande; Sara Munguakonkwa Byamungu; Jérémie Mbinze Kindenge (Orapuh Journal, 2025)
Introduction